The Accountant's Guide to the Universe : Heaven and Hell by the Numbers - Hovey, Craig, 1958- (New York : Thomas Dunne Books, 2010)
This is an entertaining book on accounting written for a general audience. It opens with a wild premise: Heaven and Hell have been outsourced to a giant company in a distant galaxy and they are now in charge of determining who goes where after death. The entire universe is scoured for an objective system that can be adapted to the task, and it is found, in the form of accounting, in the least civilized backwater of the universe, Earth! The book is also a morality tale. It demonstrates how financial scandals (a la Bernie Madoff and many others) can be pulled off with "creative accounting," and how much a person adds or subtracts from the universe by their actions. Written for anybody who has taken an accounting class, practices it for a living, or is simply interested in seeing how a system designed to record finances can also be used to judge the entire universe will be enlightened by this book.
The outsourcing of heaven and hell -- Forbidden fruit -- Mankind's one giant leap -- The first sprouting -- From follicle to forest -- From pellet to perfection -- Hair on fire -- Into the shark tank -- The perils of profit -- For whom the toupee tolls -- When a picture fakes a story -- Vacation plans -- A flounder in paradise -- To fall without grace -- A rueful reunion -- The eternally challenged -- Exercise of a lifetime -- Closing time -- Passage of the prodigal son.
Includes bibliographical references and index.
Keywords: Accounting